2011
DOI: 10.1002/jbt.20407
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo (Bubalus bubalis) epiphyseal proteins give protection from arsenic and fluoride‐induced adverse changes in acetylcholinesterase activity in rats

Abstract: The objective of this study was to determine the effect of fluoride (F) and arsenic (As) on the activity of acetylcholinesterase (AChE), a critically important nervous system enzyme, and to test the protective role of buffalo epiphyseal (pineal) proteins (BEP) in rats. Arsenic (20 mg/kg BW, intraperitoneally) and F (150 ppm, perorally) were exposed, and BEP was administered intraperitoneally (100 μ g/kg BW) along with F and As to rats for 7 days. As and F exposure significantly (p < 0.05) increased their level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The inhibition of AChE activity in as toxicity due to the free radical generation and oxidative stress induced ill effects were already reported by Bharti et al, (2012). The data obtained from this study clearly show that as significantly decreased the activity of AChE in plasma of rats.…”
Section: Discussionsupporting
confidence: 81%
“…The inhibition of AChE activity in as toxicity due to the free radical generation and oxidative stress induced ill effects were already reported by Bharti et al, (2012). The data obtained from this study clearly show that as significantly decreased the activity of AChE in plasma of rats.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, fluoride may affect the activity of some enzymes in the brain. Bharti et al (2012) confirmed that Fsignificantly reduces acetylcholine esterase (AchE) content in rat brain. Degroot et al, (2002) found that AchE can inhibit the formation of physostigmine in either the dorsal or the ventral hippocampus, resulting in increased exploratory behavior in the open arm elevated-plus maze, which was in accordance with the findings of Liu et al, (2014).…”
Section: Brain Damagementioning
confidence: 72%
“…A range of studies revealed that human and animal exposure to different levels of arsenic causing acute, sub-acute and chronic toxicity in animals (Bharti and Srivastava 2009;Bharti et al 2012a; and humans and affects their body physiology and health (Tchounwou et al, 2019;Alvarado-Flores et al, 2019). The latest global number of people infected with arsenicosis, which exceeds the World Health Organization's (WHO's) safe standard for drinking water by 10 ppb, is around 230 million, which has increased dramatically in a decade (Shaji et al, 2021).…”
Section: Introductionmentioning
confidence: 99%